The effect of cheese brine concentrations on survival of Listeria monocytogenes - Durmaz, Hisamettin; Aygun, Osman; Ardic, Mustafa (Wfl Publ, 2009)
Although storage in brine is thought to cause a decrease in the populations of undesirable microorganisms, there is great concern that the brine can also serve as a reservoir for certain salt-tolerant pathogens. Therefore, in this study, inactivation of Listeria monocytogenes at different salt concentrations and times were studied to gain a better understanding of the response of the bacterium in the brines. For this purpose, cheese brines containing 13%, 15% and 19% NaCl were inoculated with 10(3) L. monocytogenes (serotype 4b, RSKK 475) CFU/mL and stored at 4 degrees C for 0, 15, 30, 60 and 90 days. Population of the pathogen in 13% brine decreased significantly (P < 0.05) during first 30 days of storage compared to population in initial brine. However, L. monocytogenes was able to survive in 13% brine during 90 days of storage. Whereas the population of L. monocytogenes in the 15% brine decreased significantly between Days 0 to 15 of storage so that direct plating at 30, 60 and 90 days gave negative results, the same samples gave positive results after enrichment. Number of L. monocytogenes in the 19% brine decreased faster than mentioned above for other salt concentrations and the pathogen was not detected in brine after 15 days of storage by both the direct plating and enrichment. The results showed that L. monocytogenes could survive in brines, if salt concentration was not higher than 19%. In conclusion, it was suggested that brined cheeses should be stored in brines containing 19% or more NaCl for at least 15 days to prevent survival of L. monocytogenes.
Keywords: Listeria monocytogenes; brine; salt concentration